Non-modifiable and Modifiable Risk Factors in Vascular Ageing Extremes: The African-PREDICT Study - Donavan Rooi; Ruan Kruger; Esmé Jansen van Vuren; Yolandi Breet (Artery Research)
Abstract Background Cardiovascular risk factors accelerate vascular ageing beyond chronological age, hence early vascular ageing (EVA). Carotid to femoral pulse wave velocity (cfPWV) is a measure of vascular ageing and is used to identify EVA and supernormal vascular ageing (SUPERNOVA). Vascular ageing is not completely understood in African populations. Therefore, we aimed to phenotype young South African adults stratified by cfPWV extremes in terms of non-modifiable and modifiable risk factors. This study included 1133 young adults (mean age: 24.5 years). We measured cfPWV using applanation tonometry. Body composition measures, self-reported 24-h dietary intake, smoking and alcohol consumption were included. Fasting blood samples were analysed for biochemical risk factors. Three groups based on cfPWV percentiles were compared and included SUPERNOVA (≤ 10th percentile), average vascular ageing (AVA, between 10 to 90th percentile) and EVA (≥ 90th percentile). Results Chronological age, male sex, smoking, alcohol use, and blood pressure were incrementally higher across PWV groups (all p trend ≤ 0.007). Black ethnicity was higher (p = 0.038) in the SUPERNOVA group. In exploratory factor analysis, a factor pattern including mean arterial pressure and fasting glucose showed beneficial odds (OR 0.62, p = 0.002) for SUPERNOVA and higher likelihood (OR 2.10, p < 0.001) for EVA. Another factor pattern of socio-economic status and total dietary fat showed lower odds (OR 0.64, p = 0.003) for EVA. Conclusion Poor lifestyle behavioural risk factors seem detrimental in the EVA group conferring a possible higher risk of future CVD.